Erectile Dysfunction among Opiate Addicts Receiving Methadone Maintenance Therapy at Muhimbili National Hospital: A Cross-Sectional Survey (Tanzania Medical Journal, 2020)
BackgroundMethadone Maintenance Therapy (MMT) has been reported to be associated with varied grades of erectile dysfunction (ED). The extent of among methadone users in Tanzania is unknown. ED has the potential to negatively affect maintenance therapies and need to be addressed. This study therefore sought to determine the magnitude of ED among methadone maintenance therapy (MMT) among heroin users in Muhimbili National Hospital (MNH).MethodsA descriptive cross sectional hospital based study was conducted among heroin addicts who were on MMT at MMNH. Swahili version of Sexual Health Inventory Score for Men (SHIM) tool was used to assess ED with its five parameters to assess various components of sexual function and a total SHIM score was used to grade ED.  A sample size of 151 patients was calculated to be sufficient to detect an ED rate of 89% and above. Data was analyzed on SPSS version 23 where descriptive statistics were produced. P-value was set at 5% where association was calculated.ResultsA total of 151 clients were interviewed all of which were on heroin and cigarette. Only 4.6% had very high confidence of getting and keeping an erection, 9.3% always got a hard erection to penetrate, 15.2% were always able to maintain erection following penetration, 20.5% did not find it difficult to maintain an erection to completion of the intercourse, only 1.3% was always satisfied with sexual encounter and 11.3% reported not ED at all.Conclusion and recommendationED is a problem among MMT clients at MNH clinics with only about 1 in 10 of the MMT clients reported to be experiencing normal erectile function. More studies are needed to characterize the full extent and effect of ED among substance users in Tanzania.Key words: Erectile Dysfunctions, Opiate, Addicts, Methadone therapy.